Pengaruh Kinerja Kualitas Layanan, Kualitas Produk, Kepuasan Pelanggan dan Niat Beli Ulang pada Restoran Hoka-Hoka Bento di Kabupaten Tangerang - Aliya Ma'ruffi Anwar; Dihin Septyanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The fast food restaurant industry has experienced rapid growth and has become one of the important sectors in the culinary business, fast food restaurant business actors continue to innovate to meet the needs and desires of consumers. The intention to repurchase is the most important part that must be considered by restaurant business actors which directly impacts the sustainability and growth of the business. This study aims to fill the knowledge gap about the role of service quality performance on product quality, customer satisfaction, and repurchase intention in Hoka-Hoka Bento restaurant customers in the Tangerang Regency area. Data collection was obtained through a questionnaire distributed online in June 2024. The sampling method used is non-probability sampling with purposive sampling technique The data analysis technique used is Partial Least Square-Structural Equation Modeling (PLS-SEM). The results of data processing show that the performance of service quality,product quality, and customer satisfaction have a positive and significant effect on repurchase intentions. This research contributes to companies to improve service quality performance in forming repurchase intentions in consumers. Further research is expected to use a larger scale of respondents and use different platforms.